Exploring the radial evolution of interplanetary coronal mass ejections using EUHFORIA - Scolini, C. (2021)
Context. Coronal mass ejections (CMEs) are large-scale eruptions coming from the Sun and transiting into interplanetary space. While it is widely known that they are major drivers of space weather, further knowledge of CME properties in the inner heliosphere is limited by the scarcity of observations at heliocentric distances other than 1 au. In addition, most CMEs are observed in situ by a single spacecraft and in-depth studies require numerical models to complement the few available observations. Aims. We aim to assess the ability of the linear force-free spheromak CME model of the EUropean Heliospheric FORecasting Information Asset (EUHFORIA) to describe the radial evolution of interplanetary CMEs in order to yield new contexts for observational studies. Methods. We modelled one well-studied CME with EUHFORIA, investigating its radial evolution by placing virtual spacecraft along the Sun-Earth line in the simulation domain. To directly compare observational and modelling results, we characterised the interplanetary CME signatures between 0.2 and 1.9 au from modelled time series, exploiting techniques that are traditionally employed to analyse real in situ data. Results. Our results show that the modelled radial evolution of the mean solar wind and CME values is consistent with the observational and theoretical expectations. The CME expands as a consequence of the decaying pressure in the surrounding solar wind: the expansion is rapid within 0.4 au and moderate at larger distances. The early rapid expansion was not sufficient to explain the overestimated CME radial size in our simulation, suggesting this is an intrinsic limitation of the spheromak geometry applied in this case. The magnetic field profile indicates a relaxation on the part of the CME structure during propagation, while CME ageing is most probably not a substantial source of magnetic asymmetry beyond 0.4 au. Finally, we report a CME wake that is significantly shorter than what has been suggested by observations. Conclusions. Overall, EUHFORIA provides a consistent description of the radial evolution of solar wind and CMEs, at least close to their centres. Nevertheless, improvements are required to better reproduce the CME radial extension.